Problems and tendencies in innovation activity of Slovakia's enterprises during the last decade: The need of innovation management - Monika Šestáková; Edita Hekelová (Journal for East European Management Studies, 2003)
The present paper briefly characterizes main problems and trends in innovation activity of Slovak enterprises during 1990s. It is based on three questionnaire surveys (1990, 1996, 1998) in the sample of large and medium sized, mainly manufacturing companies. Even the last survey shows that internal and external barriers to innovation are still strong. Some improvement has been achieved in managers' awareness of the importance of innovation and necessity to create an internal climate supporting innovation and quality improvement. – – Dieser Beitrag beschreibt kurz die Hauptprobleme und Trends in den Innovationsaktivitäten der Slovakischen Betriebe in den 90er Jahren. Die Erkenntnisse basieren auf drei Umfragen (1990, 1996, 1998) in einer Auswahl von großen und mittleren hauptsächlich industriellen Betrieben. Selbst die letzte Umfrage zeigte noch starke interne und externe Barrieren gegen Innovation. Eine gewisse Verbesserung im Bewusstsein der Manager bezüglich der Bedeutung der Innovation und der Entwicklung eines internen Klimas zur Unterstützung der Innovation und der Qualitätsverbesserung hat sich gezeigt.
Keywords: 650; innovation activity; innovation management; quality improvement; quality management; human resource management